Composition and seasonal variation of shrimp post larvae at Matang Mangrove Ecosystem, Perak - Razali, Nur Hafiza (2016)
An investigation on composition and seasonal occurrence of shrimp post larvae was conducted in the Matang Mangrove Reservation Forest Perak, Malaysia during wet season (November 2015 to January 2016) and dry season (June 2015 to August 2015). There were three sampling stations, Station 1 (MO) at Sungai Tiram Laut, which the least disturbed mangrove, Station 2 (MT) at Sungai Tinggi, moderately disturbed mangrove and Station 3 (MS) at Sungai Sepetang which considered as a most disturbed mangrove area. None of the water parameters showed significant difference (p>0.05) among stations except only for water salinity (p<0.05). In total of 11682 individual was observed during the study period. There were four major taxa were identified namely Lucifer (23%), Acetes (3.8%), Mysid (1.7%) and Odontodactylus (0.1%) and the rest is unidentified (66.32%). The overall mean density of shrimp post larvae (PL) was calculated as 18.36 individuals/100 m3 in the investigated area. None of the diversity indices showed significant variation among the stations (p>0.05). However, all diversity indices of shrimp post larvae in study area shows statistically significant (p<0.05) difference between the wet and dry season.